2021
DOI: 10.1371/journal.ppat.1009280
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular niche-specific profiling reveals transcriptional adaptations required for the cytosolic lifestyle of Salmonella enterica

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium) is a zoonotic pathogen that causes diarrheal disease in humans and animals. During salmonellosis, S. Typhimurium colonizes epithelial cells lining the gastrointestinal tract. S. Typhimurium has an unusual lifestyle in epithelial cells that begins within an endocytic-derived Salmonella-containing vacuole (SCV), followed by escape into the cytosol, epithelial cell lysis and bacterial release. The cytosol is a more permissive environment than the SCV and su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 148 publications
(214 reference statements)
2
56
0
Order By: Relevance
“…These variations between serovars in early interactions with the host may direct the timing and magnitude of some aspects of the innate immune response, based on relative proportions of luminal to intracellular bacteria. Additionally, intracellular STM can be found in either the vacuole or the cytosol, and a recent study identified specific bacterial adaptations required for these two different intracellular lifestyles [33]. In the HIOs, we observed that some inflammatory pathways were decreased early during ST infection when compared to NTS.…”
Section: Plos Pathogensmentioning
confidence: 56%
“…These variations between serovars in early interactions with the host may direct the timing and magnitude of some aspects of the innate immune response, based on relative proportions of luminal to intracellular bacteria. Additionally, intracellular STM can be found in either the vacuole or the cytosol, and a recent study identified specific bacterial adaptations required for these two different intracellular lifestyles [33]. In the HIOs, we observed that some inflammatory pathways were decreased early during ST infection when compared to NTS.…”
Section: Plos Pathogensmentioning
confidence: 56%
“…Previous studies have shown that a small subpopulation of hyper-replicating STM resides within the cytosol of epithelial cells and serves as a reservoir for dissemination. These motile bacteria retain both SPI-1 and flagella expression, but present a low expression of SPI-2 genes, and therefore are primed for invasion [65,87,88], and fuels high luminal density that facilitates fecal shedding [89]. This expression profile is somewhat similar to the identified intracellular profile of SPA.…”
Section: Plos Pathogensmentioning
confidence: 61%
“…Recently, a similar RNA-Seq approach was applied to determine the transcriptome of STM populations that are either free-living in the cytosol or residing within the SCV of HeLa cells 8 h p.i. [65]. Earlier studies have implemented a proteomic approach to determine the expression of STM proteins within HeLa cells at 6 [66] and 18 h [30] p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Three potentially restricting conditions in the SCV lead to more PhoP activity: PhoP/Q is repressed by high Mg 2+ (18) and activated by cationic antimicrobial peptides (CAMPs) (19) or acidification (20,21). Since MCOLN2 is a divalent cation channel, PhoP/Q was most likely responding to reduced Mg 2+ concentrations, which along with Zn 2+ , are limited in SCVs (22,23). Indeed, the PhoP-activated Mg 2+ importers mgtA and mgtB were both upregulated more in bacteria inside wild-type THP-1s (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…If knocking out MCOLN2 increases Mg 2+ availability, we theorized that these transporters would be necessary to uptake that extra Mg 2+ and therefore essential for the enhanced replication inside MCOLN2 -/- host cells. To test this, we generated a double knockout (Δ mgtA Δ mgtB ), which lacks the high affinity Mg 2+ importers used in low-Mg 2+ environments, like the ≤10μM concentration in the SCV ( 22 ). The double importer mutant is killed, instead of replicating, inside THP-1s ( Fig.…”
Section: Main Textmentioning
confidence: 99%